2016
DOI: 10.1007/s00248-016-0775-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and the Origin of Saliva Influence Composition and Short Chain Fatty Acid Production of Oral Microcosms

Abstract: Nitrate is emerging as a possible health benefactor. Especially the microbial conversion of nitrate to nitrite in the oral cavity and the subsequent conversion to nitric oxide in the stomach are of interest in this regard. Yet, how nitrate influences the composition and biochemistry of the oral ecosystem is not fully understood. To investigate the effect of nitrate on oral ecology, we performed a 4-week experiment using the multiplaque artificial mouth (MAM) biofilm model. This model was inoculated with stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 65 publications
(69 reference statements)
0
56
1
Order By: Relevance
“…Prior work has demonstrated dietary nitrate can alter oral microbiome composition 63, 64. However, little is known about interaction between dietary nitrate and the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated dietary nitrate can alter oral microbiome composition 63, 64. However, little is known about interaction between dietary nitrate and the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…[190,200–204]. Using nitrate supplementation as selective pressure for bacteria capable of nitrate reduction, several studies found proliferation of Veillonella [205], Streptococcus [204], Neisseria [115], Haemophilus [204], and Rothia species[115], all previously identified as high nitrate reducers. Yet, despite these varied attempts, there remains a high degree of variability in results depending on numerous methodological factors[206], including source and sampling of sample (saliva versus oral wash versus tongue scraping), direct sampling versus culture, and choice of 16S variable region for sequencing.…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
“…Nitrite can exert pH-dependent antimicrobial effects[204,232,233] via formation of reactive secondary nitrogen oxides that can disrupt aerobic respiration[234], inhibit bacterial acid production, and disrupt biofilm formation[235237]. In settings of low pH and high nitrate and nitrite concentrations, selected bacteria and bacterial communities capable of nitrate reduction may preferentially survive or expand their population[115,205]. Indeed, increased production of the weak base, ammonia via nitrate reduction is a well-known strategy for bacteria to alkalinize their cytoplasm and local environment and protect against the potential toxic effects of high concentrations of nitrate, nitrite and NO[238].…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reads were processed into OTUs as described previously. [ 19 ] The most abundant sequence of each OTU was classified using the RDP classifier [ 20 ] and HOMD version 14.51. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%